2014
DOI: 10.1590/1413-78522014220200698
|View full text |Cite
|
Sign up to set email alerts
|

Minimal invasive ostheosintesis for treatment of diaphiseal transverse humeral shaft fractures

Abstract: OBJECTIVE: To evaluate patients with transverse fractures of the shaft of the humerus treated with indirect reduction and internal fixation with plate and screws through minimally invasive technique. METHODS: Inclusion criteria were adult patients with transverse diaphyseal fractures of the humerus closed, isolated or not occurring within 15 days of the initial trauma. Exclusion criteria were patients with compound fractures. RESULTS: In two patients, proximal screw loosening occurred, however, the fractures c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
2
12
0
1
Order By: Relevance
“…Tsai et al 7 analyzed the epidemiology of humeral shaft fractures over a five-year period in Taiwan and reported a predominance in men in the third decade of life; those authors suggested a correlation with the difference in age distribution among countries where the data were collected. Studies presenting surgical results in smaller samples, such as those by Connolly et al 8 (53 patients), Kumar et al 9 (30 patients), and Zogaib et al 10 (22 patients), are in agreement with the distribution observed in the present study, with a predominance of males between the third and fourth decades of life. A lower mean age and a higher male prevalence may be related to higher-energy trauma and to cases that were not susceptible to conservative treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Tsai et al 7 analyzed the epidemiology of humeral shaft fractures over a five-year period in Taiwan and reported a predominance in men in the third decade of life; those authors suggested a correlation with the difference in age distribution among countries where the data were collected. Studies presenting surgical results in smaller samples, such as those by Connolly et al 8 (53 patients), Kumar et al 9 (30 patients), and Zogaib et al 10 (22 patients), are in agreement with the distribution observed in the present study, with a predominance of males between the third and fourth decades of life. A lower mean age and a higher male prevalence may be related to higher-energy trauma and to cases that were not susceptible to conservative treatment.…”
Section: Discussionsupporting
confidence: 92%
“…One study was written in German [ 49 ], and the remaining studies were written in English. 24 studies were conducted in Asia [ 11 13 , 15 18 , 20 , 22 25 , 27 , 30 , 31 , 33 , 36 38 , 40 42 , 44 , 46 , 48 ], six in Europe [ 21 , 32 , 39 , 45 , 47 , 49 ], five in South-America [ 14 , 19 , 26 , 34 , 43 ], three in North-America [ 9 , 10 , 35 ] and one in Africa [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…22 studies reported on primary RNP [ 9 12 , 14 , 16 , 18 , 20 , 22 , 23 , 26 , 33 35 , 37 40 , 43 , 45 , 47 , 49 ]. These studies consisted of 922 patients of which 88 presented with primary RNP (10%) (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations